DEVELOPMENT OF A CLOUD-BASED TECHNOPRENEURSHIP LEARNING MODEL IN ICT VOCATIONAL EDUCATION (TECH2C) - Pratama, Afis; Sutarto, Sutarto; Wardani, Ratna (LPPM Universitas Jambi, 2026)
The rapid growth of digital industries and the persistent unemployment among ICT graduates indicate a competency gap between vocational education outcomes and industry demands. This study aims to develop and validate a Cloud-Based Technopreneurship Learning Model (Tech2C) to strengthen digital entrepreneurial competencies in ICT vocational education. This research employed a Research and Development (R&D) approach adapted from Borg and Gall, integrating design-based research principles. The development process involved expert validation (n=4), a limited field trial (25 students; 4 lecturers), and an expanded field trial (60 students; 6 lecturers). Data were collected using validation sheets, perception questionnaires, achievement tests, and Focus Group Discussions. Descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM) were used for analysis. The results show that the Tech2C model is highly valid (89%), highly practical (instructional quality 92%; product display 95%), and effective (82% overall effectiveness). The greatest improvement was observed in the affective domain (84%), followed by the psychomotor (82%) and cognitive (80%) domains. PLS-SEM analysis confirms that instructional quality, material quality, interactivity, flexibility, and evaluation quality significantly influence learning outcomes. The novelty of this research lies in the systematic integration of Project-Based Technopreneurship, Design Thinking processes, and cloud computing infrastructure into a unified vocational learning model that serves as both a learning ecosystem and a digital product deployment environment. The implication of this study is the provision of an empirically validated instructional framework that vocational higher education institutions can adopt to foster digital job creators rather than job seekers.